What's new in multiple sclerosis spasticity research? Poster session highlights - Linker, Ralf (Neurodegenerative Disease Management, 2017)
Each year at the Multiple Sclerosis Experts Summit, relevant research in the field of multiple sclerosis spasticity is featured in poster sessions. The main studies presented at this year's meeting are summarized herein.
EVALuna2:36316